2022
DOI: 10.3390/polym14122408
|View full text |Cite
|
Sign up to set email alerts
|

Ring-Opening Polymerization (ROP) and Catalytic Rearrangement as a Way to Obtain Siloxane Mono- and Telechelics, as Well as Well-Organized Branching Centers: History and Prospects

Abstract: PDMS telechelics are important both in industry and in academic research. They are used both in the free state and as part of copolymers and cross-linked materials. At present, the most important, practically used, and well-studied method for the preparation of such PDMS is diorganosiloxane ring-opening polymerization (ROP) in the presence of nucleophilic or electrophilic initiators. In our brief review, we reviewed the current advances in the field of obtaining polydiorganosiloxane telechelics and monofunctio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 143 publications
1
8
0
Order By: Relevance
“…Moreover, early studies on the hydrothiolation of various functional olefins showed that the presence of a heteroatom at the terminal double bond has a strong activating effect by itself that directs the reaction to the beta-position [ 21 ]. This is confirmed both by the first studies that have already become classical [ 24 ] and by more recent studies performed using computer simulation methods [ 20 ].…”
Section: Introductionsupporting
confidence: 63%
See 2 more Smart Citations
“…Moreover, early studies on the hydrothiolation of various functional olefins showed that the presence of a heteroatom at the terminal double bond has a strong activating effect by itself that directs the reaction to the beta-position [ 21 ]. This is confirmed both by the first studies that have already become classical [ 24 ] and by more recent studies performed using computer simulation methods [ 20 ].…”
Section: Introductionsupporting
confidence: 63%
“…The ratio of these processes is determined by the nature of the olefinic substrate. For example, only chain transfer is observed in the thiolation of norbornene, whereas these reactions compete in the case of acrylates [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The introduction of organic substituents and functional groups of various nature into the structure of polyorganosiloxanes is, in turn, a defining synthetic stage on the way to the creation of materials based on them. The preparation of polyorganosiloxanes with various functional groups, as well as copolymers and cross-linked materials based on them, is usually carried out using three main synthetic approaches: the hydrosilylation reaction, hydrothiolation, and ROP or catalytic rearrangement . Despite the wide distribution of these reactions and their importance for the preparation of functional polysiloxanes and materials based on them, ROP is often used in combination with addition reactions.…”
Section: Introductionmentioning
confidence: 99%
“…The latter, a resourceful product from tailings, possesses highly available SiO 2 content, rich porous structure, various forms of transition metals (Fe-, Mn-based metals, etc. ), and their oxide sites, offering great potential for the immobilization of heavy metals [ 15 , 16 , 17 ]. Apart from this, Anbia et al [ 18 ] reported that Fe 3 O 4 –copper-functionalized silicon nanowires from silicon powder were utilized as a catalyst for phenol degradation with an efficiency of approximately 100%.…”
Section: Introductionmentioning
confidence: 99%